APLIKASI SIMULASI MODEL DINAMIS PERTUMBUHAN TANAMAN UNTUK MENDUGA PRODUKSI TANAMAN PADI - Dede Dirgahayu Domiri (Indonesian National Institute of Aeronautics and Space (LAPAN), 2011)
The study was conducted to explore the physical processes and weather and its influence on the development of rice plants, and to analyze the simulation results that can be applied to predict rice crop production. Methods which used in this research are water balance model, growth and development model trough Dynamic Modeling Simulation. Results of a study showed that the optimal planting time can be predicted from the simulation model; rice yield potential can be estimated based on the maximum leaf area index, and a decrease in rice yield can be predicted from changes in ratio value of Actual and Maximum Evapotranspiration (ETa/ETm) which generated by the model.Keywords: Simulation model, Water balance, Rice crop production